ВЗАИМОСВЯЗЬ БИОХИМИЧЕСКИХ ПОКАЗАТЕЛЕЙ КРОВИ С ПРОДУКТИВНОСТЬЮ КАРАКУЛЬСКИХ ОВЕЦ ОКРАСКИ СУР СУРХАНДАРЬИНСКОГО ПОРОДНОГО ТИПА - Омонов, М.И. (SCIENCE and SOCIETY, 2019)
The article presents the results of studies on the relationship of blood biochemical parameters with the productivity of Karakul sheep coloring sur of Surkhandarya breed type. The use of sheep - producers with known biochemical parameters will allow to obtain the offspring with a large yield of elite offspring.